Pharmacist-led iodinated contrast media infusion risk assessment service - Huiyan Jiang; Yuan Li; Xiaoyan Wu; Hongming Yu; Xin Zhang; Weihong Ge; Simin Yan (Frontiers Media S.A., 2023)
Background: With the increasing development of medical imaging, the use of iodinated contrast media has become more widespread. Adverse reactions caused by iodinated contrast media have drawn much attention. Despite this, there is still a lack of unified standards for the safe infusion process of iodinated contrast media in clinical practice both domestically and internationally.Objectives: Establishing a risk management service system to better predict the risks associated with iodinated contrast media infusion, reduce the incidence of adverse reactions and minimize patient harm.Method: A prospective interventional study was carried out from April 2021 to December 2021 at Nanjing Drum Tower Hospital in China. During this study, a service system was established to manage the risks associated with the infusion of iodinated contrast media. Personalized risk identification and assessment were performed by a pharmacist-led multidisciplinary team before iodinated contrast media infusion. Early warning, prevention, and adverse reaction management were performed according to different risk levels during and after infusion.Results: A multidisciplinary team led by pharmacists was established to evaluate the risks associated with infusion of iodinated contrast media. A total of 157 patients with risk factors related to the iodinated contrast media were screened out, which prevented 22 serious adverse events and enhanced the quality of medical care. All participants expressed high satisfaction with the service.Conclusion: Through practical exploration, the pharmacist-led multidisciplinary team can provide advance warning and effectively limit the risks of adverse reactions caused by iodinated contrast media to a preventable and controllable level. This approach serves as a valuable reference for developing strategies and schemes to reduce the incidence of such reactions. Therefore, we encourage the implementation of this intervention in other areas of China.